(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
This paper stems from a research study conducted to explore the conceptions of Namibia’s Ovahimba tribe about the rights of the dead. Among other disciplines, the study locates itself under customary law, sociology and anthropology. The study employed a qualitative approach to data collection and analysis. The population of this study was all the Ovahimba speaking people living in the Kunene Region. A combination of the convenience, the purposive and the homogeneous sampling techniques were used to select the sample. The study established that Ovahimba people believe that the spirits of the dead (ancestors) live and communicate with them all the time through the sacred fire. Therefore, they believe that the dead have equal rights as the living. It is therefore recommended that the Namibian nation be wary of importation of Western values that impose themselves on indigenous African cultures in the name of law and justice. The paper also recommends that the school curriculum for the Ovahimba people be vetted to ascertain cultural fairness and neutrality to avoid elements of ideological hegemonic impositions and/or brainwash.